Long-run Relationships of Macroeconomic Variables in Nepal: A VAR Approach - Koirala, T. P. (NRB Economic Review, 2009)
This paper utilizes cointegration procedure of Johansen and Juselius (1990) in estimating the long run economic relationships of macroeconomic variables comprising M2 monetary aggregate, Real Gross Domestic Product (RGDP), Consumer Price Index (CPI) and Interest Rate (RT) using annual data ranging from 1975 to 2006. Since one cointegrating vector is found to be statistically significant among the variables under consideration, the result is tantamount to deducing the coefficients of Error Correction Model (ECM). In an application of the Augmented Dickey and Fuller (ADF) test to examine the presence of unit roots in the variables prior to the variables used in estimating long run relationships, the ADF sequential search procedure supports an existence of unit roots in all the variables. This paper also estimates the demand for money function in Nepal as an application of long run relationships between the variables using the said procedure. The coefficients of income and interest rate elasticity of M1 so estimated as depicted by the normalized cointegrating vector are in line with theoretical underpinning. Since the coefficients estimated in this paper rely on restricted VAR method that are contrary to the past practices in estimating cointegrating vector using the Engle-Granger (1987) two-step procedure in Nepal, the coefficients are supposed to be robust and consistent owing to the stronger restrictions imposed by cointegrating vector as against the a theoretical VAR approach.